THE EFFECTIVENESS OF PEDATI LEARNING DESIGN IN LEARNING EDUCATIONAL PSYCHOLOGY FOR PROSPECTIVE TEACHERS OF ISLAMIC RELIGIOUS EDUCATION - Abdillah, Hamdi; Jannah, Miftahul (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
This research is motivated by the fact that studying educational psychology is very important. By understanding educational psychology, prospective Islamic religious education teachers can form Islamic personalities in students through understanding behavior and stages of development. Educational psychology is also a bridge in realizing good social interaction between teachers and students, between teachers, or between students and other parties. This research aims to determine the effectiveness of the PEDATI learning design in educational psychology learning for prospective Islamic religious education teachers. The approach in this research is a mixed method with a survey method. The respondents in this study were students taking Educational Psychology courses. The research results show that the PEDATI learning design implemented is in the medium category, and respondents perceive its effectiveness as good. Student perspective Islamic religious education teachers become better prepared for learning, and discussions in learning become more lively, especially in analyzing student growth and development, student environment, differences in student character, and student potential.